Inhibition of proliferation and induction of autophagy by atorvastatin in PC3 prostate cancer cells correlate with downregulation of Bcl2 and upregulation of miR-182 and p21. - Xinjian Peng; Wenping Li; Liang Yuan; Rajendra G Mehta; Levy Kopelovich; David L McCormick (PLoS ONE)
The epidemiologic association between statin use and decreased risk of advanced prostate cancer suggests that statins may inhibit prostate cancer development and/or progression. Studies were performed to determine the effects of a model statin, atorvastatin (ATO), on the proliferation and differentiation of prostate cancer cells, and to identify possible mechanisms of ATO action. ATO inhibited the in vitro proliferation of both LNCaP and PC3 human prostate cancer cells in a dose- and time-dependent fashion. The greater inhibitory activity of ATO in PC3 cells was associated with induction of autophagy in that cell line, as demonstrated by increased expression of LC3-II. miR-182 was consistently upregulated by ATO in PC3 cells, but not in LNCaP cells. ATO upregulation of miR-182 in PC3 cells was p53-independent and was reversed by geranylgeraniol. Transfection of miR-182 inhibitors decreased expression of miR-182 by >98% and attenuated the antiproliferative activity of ATO. miR-182 expression in PC3 cells was also increased in response to stress induced by serum withdrawal, suggesting that miR-182 upregulation can occur due to nutritional stress. Bcl2 and p21 were identified to be potential target genes of miR-182 in PC3 cells. Bcl2 was downregulated and p21 was upregulated in PC3 cells exposed to ATO. These data suggest that miR-182 may be a stress-responsive miRNA that mediates ATO action in prostate cancer cells.